Evaluation of the visual attractiveness of the landscape in selected areas in Poland - Podhorodecka, Katarzyna (Turyzm/Tourism, 2016)
In the article photographs presenting the natural landscape of various areas of Poland: lowlands, highlands, lake districts, mountains, cliffs and dune coastlines, have been analyzed. Moreover, photographs presenting diverse natural landscapes in a single image were selected too. The purpose of this article is to answer to the following questions: Do tourists appreciate diverse natural landscapes more highly?; Is there any difference between men and women?; Do national tourists differ from foreign tourists? The study was conducted among a group of 174 students of Geography and Spatial Development as well as among foreign students who had come to Poland on the Erasmus program. The research took place between October 2015 and May 2016.